Pemanfaatan Aplikasi Quizizz sebagai Evaluasi Pembelajaran Matematika pada Siswa Sekolah Dasar - Abu Zaeni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
The advancement of information and communication technology has significantly impacted the field of education, particularly at the elementary school (SD) level. In this context, the utilization of educational applications such as Quizizz as an evaluation tool in mathematics learning becomes an intriguing and relevant alternative. This research aims to achieve two main objectives: 1) To identify the ways Quizizz is used as an evaluation tool in mathematics learning, and 2) To analyze inhibiting factors that impede the optimization of Quizizz application utilization. To attain these goals, the research adopts a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research findings indicate that 1) teachers can create mathematics quizzes with various question formats, including multiple-choice, jumble, and true/false, and incorporate images or videos as supporting materials. Students can access the quizzes using specific codes provided by the teachers. 2) There are inhibiting factors such as dependence on network or internet connectivity, potential for cheating, challenges in time management, and difficulties in finding suitable time, which need to be addressed to ensure that the application can provide maximum benefits in mathematics learning at the elementary school level.